2016
DOI: 10.1364/ol.41.000622
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of a 400  Gbit/s orbital angular momentum multiplexed free-space optical link over 120 m

Abstract: Ren, Y. et al. (2016) Experimental characterization of a 400 Gbit/s orbital angular momentum multiplexed free-space optical link over 120 m. Optics Letters, 41(3), pp. 622-625.There may be differences between this version and the published version. You are advised to consult the publisher's version if you wish to cite from it.http://eprints.gla.ac.uk/115873/ Free-space optical (FSO) communications has attracted much attention for a variety of applications, such as back-haul and data centers [1, 2]. Given the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
64
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 153 publications
(64 citation statements)
references
References 19 publications
0
64
0
Order By: Relevance
“…In a similar fashion, in [102] a transmission rate of 1.036 Pbps with a spectral efficiency of 112.6 bps/Hz has been achieved by multiplexing 54.139 Gbps OFDM-8QAM signals over 368 wavelengths, 2 polarization states and 26 OAM modes. In addition to these lab-scale high-rate data experiments, a 400 Gbps transmission rate has been achieved over an outdoor link of about 120m by using 100 Gbps QPSK signals on 4 OAM modes [103].…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…In a similar fashion, in [102] a transmission rate of 1.036 Pbps with a spectral efficiency of 112.6 bps/Hz has been achieved by multiplexing 54.139 Gbps OFDM-8QAM signals over 368 wavelengths, 2 polarization states and 26 OAM modes. In addition to these lab-scale high-rate data experiments, a 400 Gbps transmission rate has been achieved over an outdoor link of about 120m by using 100 Gbps QPSK signals on 4 OAM modes [103].…”
Section: Challenges and Solutionsmentioning
confidence: 99%
“…Ren et al [40] reported a 400 Gbit s −1 data link over 120 m by multiplexing four OAM beams with = −3, −1, +1 and +3. As shown in figure 7, the transmitter and receiver were located at the same site on the roof of (d) Link parameter design for orbital angular momentum-based free-space optical systems…”
Section: (C) Orbital Angular Momentum-based Free-space Optical Links mentioning
confidence: 99%
“…In the integrated optical devices, phase, amplitude, and polarization of the electric field of the optical communication signal are modulated using miniaturized waveguides with straight or interferometric configurations 21 . As it is mentioned above, one of the possible approaches to increase the capacity of an optical 7, 2224 or quantum 9 channel is the using of an optical signal carrying OAM . Although integrated optically generation, detection, multiplexing, and switch of the optical signals with different OAM values are demonstrated 25–32 , but neither modulators nor switches for manipulating a specific guided mode carrying OAM integrated optically have been proposed.…”
Section: Introductionmentioning
confidence: 99%